Former and current trend in subsurface irrigation systems - Alrubaye, Yasir Layth; Yusuf, Badronnisa (Universiti Putra Malaysia Press, 2021)
The main purpose of this review is to find the diversity in research studies of subsurface irrigation systems in the past two decades. Two periods of five years were selected to reflect the research studies at the beginning and the end of the comparing periods range. A statistical sorting was used to investigate the distribution of papers according to objectives, types of irrigation systems, research methods, and limitations of the studies. Results showed that the measurements and evaluations were the most presented objectives of the selected papers for both periods. Furthermore, almost 90 percent of the recent papers used multiple research methods, unlike the papers published in the former period which only 56 percent of them used multiple methods. Also, more than 90 percent of the recent papers used a single irrigation system. In conclusion, knowledge of subsurface irrigation systems had been advanced in the former studies mostly by analyzing the measurements and evaluations of the traditional irrigation systems. Unlike the former period, the advancement in knowledge has been produced in the current period by introducing new subsurface irrigation systems and more concentration by the order of measurements, evaluation, and designing, respectively.